IMPROVING HIGH SCHOOL STUDENT’S CRITICAL THINKING ABILITY THROUGH DIGITAL MEDIA ASSISTED BY LECTORA INSPIRE ON LIGHTWAVE MATERIAL - Raldy Aditya; Raldy Aditya; Uwes Anis Chaeruman; Moch. Sukardjo (JURNAL SPEKTRA, 2022)
This research is motivated by the critical thinking abilities of senior high school (SMA) students who are low in several regions in Indonesia. This study aims to determine the effect of the application of digital media assisted by Lectora inspire on the critical thinking skills of eleven-grade students on light waves. The study was conducted at SMA N 25 Central Jakarta for four weeks in April 2021 with a sample of 72 students. The sample was selected with purposive sampling, which consisted of 36 students in the first eleventh-grade science class (control group) and 36 students in the second science class (experimental group). The research method used is quasi-experiment with the research design of nonequivalent control groups. The results of the posttest hypothesis test through the Mann Whitney U test with a significance level of 5% were obtained by sig. Value (2-tailed) 0.001. The zero hypothesis is rejected (Lectora inspires the influence of media on student critical thinking skills). Critical Thinking Ability Students Experimental Group increased higher (n-gain 0.5 middle category) than the control group (N-gain 0.06 low categories). Students respond very well (83%) to this lesson. Application of Inspire Lectora learning media has an impact on improving student critical thinking skills.